'It is stigma that makes my work dangerous': experiences and consequences of disclosure, stigma and discrimination among sex workers in Western Australia. Issue 2 (1st February 2022) - McCausland, Kahlia; Lobo, Roanna; Lazarou, Mattea; Hallett, Jonathan; Bates, Julie; Donovan, Basil; Selvey, Linda A.
Abstract: Western Australia criminalises sex work whilst some other Australian jurisdictions have decriminalised the industry. This article examines the role of Western Australia's legislation in reinforcing stigma and discrimination of sex workers. It draws on stigma and discrimination-specific results from open-ended survey responses and interview data collected as part of a larger cross-sectional mixed-methods study. Experiences and/or anticipation of stigma and discrimination resulted in some sex workers concealing their involvement in sex work from family, friends and their home communities. This was a major barrier to accessing health care and protective services and impacted negatively on their mental health and wellbeing. There is a need for policy change and support to shift society's perception of sex work to that of a legitimate occupation to decrease sex workers' experiences of stigma and discrimination and improve their access to and utilisation of health care and protective services. These findings highlight the need for the decriminalisation of the Western Australian sex industry and the development of training programmes for police and healthcare workers to reduce the stigma and discrimination experienced by sex workers in these settings.